Evaluating the effectiveness of trend analysis algorithms for diagnosing turbine engine - Кучер, О.Г.; Власенко, П.О.; Тишкевич, О.В. (Proceedings of National Aviation University (archive), 2006)
In this article are examined questions of diagnostics of aircraft engine and, in the first place, the analysis of the effectiveness of the methods of trend analysis as one of the most important procedures of the detection of defect, is carry ouied.